Using The TGT Learning Model to Improve Student Learning Outcomes in Colloidal Systems Material at Sman 1 Lhoknga Aceh Besar - Mardhiah, Ainun; Adiska, Dessi Nur; Astryna, Syarifah Yanti; Rahmi, Rauzatur (Universitas Lampung, 2024)
The learning model is one of the important things that must be prepared by an educator in learning process. One effort to achieve value in understanding concepts and learning outcomes can be done by implementing active, creative, fun and effective learning models in the classroom. The innovation that can be carried out is by implementing the Teams Games Tournaments (TGT) learning model. The purpose of this research to improve learning outcomes, determine student activities and responses to the subject of colloid systems using the teams games torunament (TGT) learning model in class XI at SMAN 1 Lhoknga Aceh Besar. The design used in this research was nonequivalent control group design. The sampling technique used was purposive sampling. The subjects of this research were class XI IA1 and class XI IA2, totaling 24 students. Research data was obtained from learning outcomes tests. observation of student activities, and provide student response questionnaires. The research results show that 1) The use of the teams games tournament (TGT) learning model can improve student learning outcomes in the Colloid System material at SMAN 1 Lhoknga Aceh Besar with an average score of 79,54%. 2) Student activity in teaching and learning activities through the use of the teams games tournament (TGT) learning model at the first meeting obtained a percentage of 75%, while at the second meeting student activity increased with a percentage of 90%. 3) Student responses to the use of the teams games tournament (TGT) learning model in the questionnaire distributed at the end of the lesson were obtained sequentially, namely strongly agree 28%, agree 58% and disagree 14%.Keywords: Teams Games Tournament (TGT) learning model, learning outcomes, colloid system DOI: 10.23960/jppk.v13i2.29811